LEARN PRENEUR COLLABORATION: RESILIENCE FOR SMES IN TIMES OF TECHNOLOGICAL CHANGE - Gutiérrez, María Cecilia; Moreno, Juan José Jiménez; Ascúa, Rubén (Jurnal Administrasi Bisnis, 2025)
The article aims to contribute to the discussion about how collaboration helps SMEs to face the incorporation of digital technologies related to Industry 4.0. Employing a systemic perspective, data was gathered through surveys and interviews with manufacturing SMEs and Knowledge Subsystem (KS) actors in Santa Fe, Argentina. Findings confirm that SMEs implement Industry 4.0 projects with heterogeneous learning processes and outcomes, where collaboration—both internal among teams and external with partners, suppliers, and the KS—emerges as a determining factor. In fact, the KS plays a vital role in providing relevant solutions, fostering absorptive capacity, and enabling proactive adaptation and resilience. High strategic concordance between SMEs and KS actors' views on technological objectives and collaboration streamline the adoption of increasingly complex technologies. SMEs are advancing technologically through incremental steps, strategically selecting technologies and partners that supports the implementation of innovations. In this process, collaboration functions as a critical enabler, reinforcing the role of tacit knowledge and leveraging public financing to enhance absorptive capacity and ensure the sustainable integration of new solutions.